Traditional house painting, architecture, decorative motifs and their cosmological underpinnings: the case of ward 17 Matobo district. - Dube, Quiet (Midlands State University, 2018)
The study focuses on the shapes of buildings, decorative motifs and their cosmological underpinnings. The symbols are so engrained into a people’s culture that when people see these symbols they do not get the messages infused on the symbols. The thrust of this study is to unpack the cosmogonies, worldview and philosophy of life embedded on the designs and decorative motifs executed on houses in Matobo district. The study is qualitative and relied on interviews, observations and pictures as source of data. The study is guided by Cultural Relativism approach and Semiotics theory. The study found out that architectural designs and decorative symbols are imbued with messages, warnings and advices directed to the society and those outside the society of Matobo to have an understanding about that particular society. These motifs reveal the cosmos, social relations, responsibilities, totems, nature or environment and the history of the producers of art. It is also concluded here that the architectural shapes and decorative motifs tell a story about the artist, the society he/she lives in and can bring out his/her history and life experiences as well as how they interpret the environment they live in. The study recommends that other researchers should also cover and unpack the philosophy of a people embedded on General Dealer Stores and Bottle Stores inscriptions. It also recommends that the responsible ministry should establish initiatives that revitalise the practice of traditional house painting as it reveals more about a people and their philosophy as well as cosmogonies. The study concludes that symbols and designs are means of communication and expressing one’s self.